10th International Conference on Robotics, Vision, Signal Processing and Power Applications Enabling Research and Innovation Towards Sustainability - Zawawi, Mohamad Adzhar Md.; Teoh, Soo Siang; Abdullah, Noramalina Binti; Mohd Sazali, Mohd Ilyas Sobirin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This proceedings book presents a collection of research papers from the 10th International Conference on Robotics, Vision, Signal Processing & Power Applications (ROVISP 2018), which serves as a platform for researchers, scientists, engineers, academics and industrial professionals from around the globe to share their research findings and development activities. The book covers various topics of interest, including, but not limited to: •Robotics, Control, Mechatronics and Automation •Vision, Image, and Signal Processing •Artificial Intelligence and Computer Applications •Electronic Design and Applications •Biomedical, Bioengineering and Applications •RF, Antenna Applications and Telecommunication Systems •Power Systems, High Voltage and Renewable Energy •Electrical Machines, Drives and Power Electronics •Devices, Circuits and Embedded Systems •Sensors and Sensing Techniques.
Robotics, Control, Mechatronics and Automation -- Vision, Image, and Signal Processing -- Artificial Intelligence and Computer Applications -- Electronic Design and Applications -- Biomedical, Bioengineering and Applications -- RF, Antenna Applications and Telecommunication Systems -- Power Systems, High Voltage and Renewable Energy -- Electrical Machines, Drives and Power Electronics -- Devices, Circuits and Embedded Systems -- Sensors and Sensing Techniques.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Signal processing; Electric power production; Control, Robotics, Automation; Artificial Intelligence; Signal, Speech and Image Processing; Electrical Power Engineering